Uncertainties associated with assessing the public health risk from Legionella - Whiley, Harriet; Keegan, Alexandra; Fallowfield, Howard; Ross, Kirstin (Frontiers in Microbiology, 2014)
Legionella is an opportunistic pathogen of public health concern. Current regulatory and management guidelines for the control of this organism are informed by risk assessments. However, there are many unanswered questions and uncertainties regarding Legionella epidemiology, strain infectivity, infectious dose and detection methods. This review follows the EnHealth Risk Assessment Framework, to examine the current information available regarding Legionella risk and discuss the uncertainties and assumptions. This review can be used as a tool for understanding the uncertainties associated with Legionella risk assessment. It also serves to highlight the areas of Legionella research that require future focus. Improvement of these uncertainties will provide information to enhance risk management practises for Legionella, potentially improving public health protection and reducing the economic costs by streamlining current management practises.